Why Countable Additivity?. (5th August 2013) - Easwaran, Kenny
<x xml:space="preserve">Abstract</x> It is sometimes alleged that arguments that probability functions should be countably additive show too much, and that they motivate uncountable additivity as well. I show this is false by giving two naturally motivated arguments for countable additivity that do not motivate uncountable additivity.